Home food availability, food insecurity and nutrition knowledge are key factors influencing dietary diversity among adolescent girls in Southern Ethiopia - Kim, Sunny S.; Sununtnasuk, Celeste; Tadesse, Amare W.; Oumer, Abdulaziz; Walissa, Tamirrat; Sanghvi, Tina; Menon, Purnima (American Society for Nutrition, 2020)
In Ethiopia, where 40% of the population is under 15 years, evidence on adolescent nutrition is limited. We examined the dietary diversity and its determinants among in-school adolescent girls in 2 regions in southern Ethiopia.